2018
DOI: 10.24264/icams-2018.ix.2
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Optimization of an in-situ Copper-Modified Glassy Carbon Electrode

Abstract: Square wave anodic stripping voltammetry (SWASV) technique is one of the most used electrochemical techniques in the determination of the trace amounts of heavy metals in different environments. This is due among other reasons to the fact that this method offers low detection limit, high selectivity and precision at relatively low cost. Modified film electrodes have been found as good replacement to the mercury electrodes. In this work different deposition potentials have been used to optimize an in situ-prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The high corrosion resistance of aluminum and its alloys is credited to the formation of a passive oxide film (Al 2 O 3 ) on the surface, which is thin, compact, and adherent. This film is amphoteric and can suffer localized attack when the aluminum is exposed to acid or alkaline solutions and as well as in solutions with the presence of chlorides . Hydrochloride acid is very often used to clean the aluminum surface before some industrial processes, such as hot‐dip coating or electroplating, in order to remove scales and dust, but it can cause severe corrosion .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The high corrosion resistance of aluminum and its alloys is credited to the formation of a passive oxide film (Al 2 O 3 ) on the surface, which is thin, compact, and adherent. This film is amphoteric and can suffer localized attack when the aluminum is exposed to acid or alkaline solutions and as well as in solutions with the presence of chlorides . Hydrochloride acid is very often used to clean the aluminum surface before some industrial processes, such as hot‐dip coating or electroplating, in order to remove scales and dust, but it can cause severe corrosion .…”
Section: Introductionmentioning
confidence: 99%
“…This film is amphoteric and can suffer localized attack when the aluminum is exposed to acid or alkaline solutions and as well as in solutions with the presence of chlorides . Hydrochloride acid is very often used to clean the aluminum surface before some industrial processes, such as hot‐dip coating or electroplating, in order to remove scales and dust, but it can cause severe corrosion . Thus, the corrosion control in aluminum and aluminum alloys is very important for some practical applications in the industry .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is confirmed that 2xxx, 5xxx and 7xxx aluminium alloys are susceptible to stress-corrosion cracking [5]. Moreover, evidence of corrosion in aluminium is confirmed [6]. Further scholarly articles Open circuit potential E oc À0.713 À0.723 À0.703 reported also indicate that aluminium and its alloys corrode, despite its formation of a natural oxide layer that is chemically inert [7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 66%